Preparation method of polyanionic sodium-ion battery cathode material with interface modification layer

CN116885149BActive Publication Date: 2026-10-30SHENZHEN JANAENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311075169.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-08-14
Filing Date
2023-08-24
Publication Date
2026-10-30
Estimated Expiration
2043-08-24

AI Technical Summary

Benefits of technology

第一、电化学性能优异,纳米态金属氧化物费米能级禁带宽度较窄,电子跃迁能垒较低,具有较高的电子传输能力,其在材料界面的均匀包覆可有效提高材料颗粒间的电子传输能力,进而降低电极欧姆电阻,提高电极的倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116885149B_ABST
    Figure CN116885149B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a polyanionic sodium ion battery positive electrode material with an interface modification layer, and comprises the following steps: S1, preparation of a precursor solution: uniformly dispersing a sodium source, a metal M source, an anion source and a carbon source in water to obtain a precursor solution; S2, preparation of a pre-crystalline precursor powder: performing high-temperature pyrolysis on the precursor solution obtained in the step S1 under the protection of a protective atmosphere to obtain a pre-crystalline precursor powder; S3, pre-coating of the precursor powder: mixing the pre-crystalline precursor powder obtained in the step S2 with a nano-state metal conductive oxide in proportion and performing interface modification in a high-temperature coating machine to form a uniform pre-coated powder; and S4, high-temperature sintering preparation: performing high-temperature sintering on the pre-coated powder obtained in the step S3 in a protective atmosphere to obtain the polyanionic sodium ion battery positive electrode material with the interface modification layer. The application has the characteristics of excellent electrochemical performance, good uniformity and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, specifically to a method for preparing a polyanionic sodium-ion battery cathode material with an interface modification layer. Background Technology

[0002] Sodium resources are abundant and mining costs are low. Furthermore, sodium-ion batteries operate on the same principle as lithium-ion batteries, and can, to some extent, replace lithium-ion batteries in applications such as low-speed electric vehicles and large-scale energy storage. The cathode material of sodium-ion batteries has a decisive influence on the cost and energy density of the sodium-ion battery system.

[0003] Currently, the most widely produced sodium-ion battery cathode materials on the market are layered oxides and polyanionic materials. Layered oxides have high capacity, high compaction density, and high energy density, but they suffer from multi-stage phase transitions during sodium insertion / extraction, and the dissolution of transition metal ions at the oxide interface leads to poor cycle stability, failing to meet the cycle life requirements of large-scale energy storage. They only show some application potential in the low-end power sector. Compared to layered oxides, polyanionic materials, with their ultra-high structural stability, moderate reversible capacity, and excellent cycle stability, have become the best choice for sodium-ion battery cathode materials for large-scale energy storage. Currently, the main polyanionic materials on the market include Fe-based sulfates such as Na2Fe2(SO4)3, V-based phosphates such as Na3V2(PO4)3 and NaVPO4F, Fe-based phosphates such as Na4Fe3(PO4)2P2O7, and Mn-based phosphates such as Na3MnTi(PO4)3.

[0004] The three-dimensional framework of polyanionic materials endows them with extremely high structural and thermodynamic stability, especially in Na+. + During insertion / extraction processes or exposure to humid air, the structural changes of polyanionic materials are minimal, and their electrochemical performance is well preserved. Therefore, the market currently positions polyanionic materials in the energy storage field. However, polyanionic materials have a wide band gap, long electronic transition distance, and low electronic conductivity, which cannot meet the market requirements for high-power cell systems.

[0005] From a structural perspective, polyanionic materials often contain PO4. 3- SO4 2- P2O7 4- Tetrahedral / octahedral groups often exhibit charge transfer along the TM-OP / SO-TM pathway, resulting in longer transition distances and lower electronic conductivity. Traditional carbon coating processes are commonly used in lithium iron phosphate (LFP) battery cathode materials, but for polyanionic sodium-ion battery cathode materials with generally lower sintering temperatures, carbon coating is insufficient to provide high electronic conductivity, and its uniformity is also a significant drawback. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a polyanionic sodium-ion battery cathode material with an interface modification layer, which has the characteristics of excellent electrochemical performance, good uniformity and high stability.

[0007] This invention can be achieved through the following technical solutions: This invention discloses a method for preparing a polyanionic sodium-ion battery cathode material with an interface modification layer, comprising the following steps: S1: Preparation of precursor solution: Sodium source, metal M source, anion source and carbon source are dispersed evenly in water according to the stoichiometric ratio in the molecular formula of polyanionic cathode material to obtain precursor solution. S2; Preparation of precrystalline precursor powder: The precursor solution obtained in step S1 is subjected to high-temperature pyrolysis under a protective atmosphere to obtain precrystalline precursor powder; S3: Precursor powder pre-coating: The pre-crystalline precursor powder obtained in step S2 is mixed with nano-sized metal conductive oxide in a certain proportion and the interface is modified in a high-temperature coating machine to form a uniform pre-coated powder. S4: High-temperature sintering preparation: The pre-coated powder obtained in step S3 is sintered at high temperature in a protective atmosphere to obtain a polyanion-type sodium-ion battery cathode material with an interface modification layer.

[0008] In this invention, a combined approach is adopted, consisting of preparing a pre-crystalline precursor powder, pre-coating the precursor powder, and finally high-temperature sintering. This approach has several advantages: Firstly, in terms of processability, the nano-sized metal oxide grains are small with a large specific surface area, making them easy to disperse during mixing with polyanionic materials. This reduces equipment requirements, simplifies the process, and allows for mass production. Secondly, in the sodium ion transport path control chamber, the high-temperature pyrolysis process allows for the initial formation of a pre-crystalline state with intact, small grains, which helps shorten the diffusion distance of sodium ions within the structure. Simultaneously, the uniform nano-sized metal oxide coating provides a rapid channel for electron transport. Thirdly, regarding batch consistency control, the high-temperature coating method achieves the fusion of the nano-sized metal oxide with the pre-crystalline precursor powder interface. This process is simple and controllable, effectively improving batch stability and consistency. Therefore, steps S2 to S4 are mutually reinforcing, ultimately achieving uniform coating of the conductive interface modification layer to improve electrochemical performance while simultaneously controlling the process to promote consistency.

[0009] Furthermore, in step S2, the medium-high temperature pyrolysis temperature range is 200~500℃. Under these temperature conditions, the material has low crystallinity, small grain size, and uniform distribution, which is beneficial for the uniform modification of the oxide layer at the material interface in the later stage. When the pyrolysis temperature exceeds 500℃, some molten salt will decompose and volatilize in gaseous form, leading to an imbalance in the elemental ratio, phase separation of the material, and a significant decrease in capacity. When the pyrolysis temperature is below 200℃, the material cannot form effective crystal nuclei and will exist in an amorphous ionic bonded state, which is not conducive to the coating of nanoscale metal conductive oxides in step S3, and will lead to the damage of the electron transport network, affecting the rate performance of the material. In addition, when the pyrolysis temperature is below 200℃, the loss of material crystal nuclei is not conducive to the epitaxial growth of the material along the crystal nuclei during the sintering process in step S4, and it is impossible to effectively generate a large and complete single crystal structure.

[0010] Further, in step S3, the nanoscale conductive metal oxide is one or more of ruthenium dioxide, tin dioxide, indium tin oxide, indium oxide, nickel oxide, iron oxide, silver oxide, zinc oxide, potassium oxide, aluminum oxide, and / or copper oxide. The particle size of the nanoscale conductive metal oxide is 0~20nm. When the particle size exceeds this range, the larger oxide particles cannot form a continuous and uniform coating layer on the material surface, affecting the coating effect.

[0011] Furthermore, in step S3, the nano-state metal conductive oxide accounts for 0.1~10% of the weight of the pre-crystalline precursor powder, and the primary grain size of the pre-crystalline precursor powder is 400-700nm, which is about 40-70 times that of the nano-state metal conductive oxide. Within this weight range, the nano-state metal conductive oxide is sufficiently embedded uniformly into the surface of the pre-crystalline precursor powder, and plays the role of electron transport by bonding between material particles with anions-oxygen (PO, SO, etc.).

[0012] Furthermore, in step S3, the high-temperature coating temperature range is 300~500℃. Under this temperature condition, the material has low surface tension and good fluidity, which is conducive to the full mixing and adhesion of the material and the conductive oxide. When the coating temperature exceeds 500℃, the material begins to crystallize and grow. However, as a rigid material, the nano-state metal conductive oxide is prone to crystal damage during the mixing, grinding, and coating process, affecting the epitaxial growth of the crystal in step S4. When the coating temperature is below 300℃, the bonding force between the nano-state metal conductive oxide and the material is weak, and it cannot effectively adhere to the surface of the material to form a uniform coating layer.

[0013] Furthermore, in step S4, the high-temperature sintering temperature range is 500~750℃, and the sintering time is 1~20H. At this temperature, the pre-crystallized precursor powder will further crystallize and grow to form a complete single crystal structure. The conductive oxide at its interface has low reactivity at this temperature and cannot react with the material to form a solid solution. Finally, it is embedded in the surface of the material in an intercalation form to achieve the purpose of electron transfer.

[0014] Furthermore, in step S1, the method of uniform dispersion is one or more of the following: aqueous solution dissociation, sand milling and / or ball milling, which achieve ionic dispersion of raw materials in the form of mechanical force or shear force.

[0015] Furthermore, in step S2, the protective atmosphere is nitrogen and / or argon, which is a non-oxygen-containing gas, effectively preventing the oxidation and loss of carbon source and ensuring the reduction of transition metal elements during the sintering process of the material.

[0016] Preferably, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxalate, sodium formate, sodium acetate, sodium sulfate, sodium chloride, sodium nitrate, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium dodecyl sulfonate, sodium citrate, and / or sodium polyacrylate.

[0017] Preferably, the metal source M is an Fe source, a Mn source, a V source, and / or a Ti source; the Fe source is one or more of ferric nitrate, ferric sulfate, ferric hydroxide, ferric oxide, ferric oxide, and / or ferric oxide; the Mn source is one or more of manganese oxide, manganese trioxide, manganese tetroxide, manganese hydroxide, manganese acetate, manganese nitrate, and / or manganese sulfate; the V source is one or more of vanadium pentoxide and / or ammonium metavanadate; and the Ti source is one or more of titanium dioxide, titanium sulfate, tetrabutyl titanate, isopropyl titanate, and / or titanium oxysulfate.

[0018] Preferably, the carbon source is one or more of citric acid, glucose, sucrose, starch, polyethylene glycol, polyacrylic acid, polyvinyl alcohol, graphene, carbon nanotubes and / or carbon black.

[0019] Furthermore, the positive electrode material of the polyanionic sodium-ion battery is sodium iron phosphate, sodium fluorinated iron phosphate, NASICON-type sodium vanadium phosphate, sodium fluorinated vanadium phosphate, sodium vanadium oxyphosphate, sodium fluorinated vanadium oxyphosphate, sodium iron sulfate, sodium fluorinated iron sulfate, sodium manganese titanium phosphate, sodium manganese vanadium phosphate, sodium manganese iron phosphate, sodium pyrophosphate, sodium pyrophosphate, sodium iron phosphate, sodium titanium phosphate, etc., or modified materials of the above materials.

[0020] This invention provides a method for preparing a polyanionic sodium-ion battery cathode material with an interface modification layer, which has the following beneficial effects: First, it has excellent electrochemical performance. The Fermi level band gap of nanoscale metal oxides is narrow and the electronic transition energy barrier is low, which gives it a high electron transport capability. Its uniform coating at the material interface can effectively improve the electron transport capability between material particles, thereby reducing the ohmic resistance of the electrode and improving the rate performance of the electrode.

[0021] Secondly, it exhibits good uniformity. The nanoscale metal oxide has a high lattice energy, and its decomposition temperature is much higher than that of polyanionic materials. Therefore, during sintering, it does not embed itself into the bulk structure of the polyanionic material, but instead bonds to the material surface in the form of P / SO bonds to form a metal coating layer, effectively mitigating particle pulverization caused by volume expansion during sodium insertion / extraction.

[0022] Third, it has high stability. Nanoscale metal oxides are inert materials with low interfacial activity. Their uniform coating on the material interface effectively reduces the oxidative erosion of the material by the electrolyte, increases the interfacial stability of the material to a certain extent, avoids the collapse and rock salting of the crystal structure at the material interface, and improves the cycling stability of the material. Attached Figure Description

[0023] Figure 1 EDS spectrum of Na4Fe3(PO4)2P2O7 / C / CuO material in Application Example 1; Figure 2 The charge-discharge curves of the electrode materials in Example 1 and Comparative Example 1 at 0.1C during the first week are shown. Figure 3 Rate performance curves of the electrode materials in Example 1 and Comparative Example 1; Figure 4 The figure shows the cycle performance curves of the electrode materials in Application Example 1 and Comparative Example 1. Detailed Implementation

[0024] To enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention will be further described in detail below with reference to embodiments and accompanying drawings.

[0025] like Figures 1-2 As shown, this invention discloses a method for preparing a polyanionic sodium-ion battery cathode material with an interface modification layer, comprising the following steps: S1: Preparation of precursor solution: Sodium source, metal M source, anion source and carbon source are dispersed evenly in water according to the stoichiometric ratio in the molecular formula of polyanionic cathode material to obtain precursor solution. S2; Preparation of precrystalline precursor powder: The precursor solution obtained in step S1 is subjected to high-temperature pyrolysis under a protective atmosphere to obtain precrystalline precursor powder; S3: Precursor powder pre-coating: The pre-crystalline precursor powder obtained in step S2 is mixed with nano-sized metal conductive oxide in a certain proportion and the interface is modified in a high-temperature coating machine to form a uniform pre-coated powder. S4: High-temperature sintering preparation: The pre-coated powder obtained in step S3 is sintered at high temperature in a protective atmosphere to obtain a polyanion-type sodium-ion battery cathode material with an interface modification layer.

[0026] Furthermore, in step S2, the medium-high temperature pyrolysis temperature range is 200~500℃. Under this temperature condition, the material has low crystallinity, small grain size, and uniform distribution, which is beneficial to the uniform modification of the oxide layer at the material interface in the later stage.

[0027] Further, in step S3, the nano-state metal conductive oxide is one or more of ruthenium dioxide, tin dioxide, indium tin oxide, indium oxide, nickel oxide, iron tetroxide, silver oxide, zinc oxide, potassium oxide, aluminum oxide and / or copper oxide.

[0028] Furthermore, in step S3, the nano-state metal conductive oxide accounts for 0.1~10% of the weight of the pre-crystalline precursor powder. Within this range, the nano-state metal conductive oxide can be effectively embedded in the surface of the pre-crystalline precursor powder to achieve the purpose of electron transport.

[0029] Furthermore, in step S3, the high-temperature coating temperature range is 300~500℃. Under this temperature condition, the material has low surface tension and good fluidity, which is conducive to the full mixing and adhesion of the material and the conductive oxide.

[0030] Furthermore, in step S4, the high-temperature sintering temperature range is 500~750℃, and the sintering time is 1~20H. At this temperature, the pre-crystallized precursor powder will further crystallize and grow to form a complete single crystal structure. The conductive oxide at its interface has low reactivity at this temperature and cannot react with the material to form a solid solution. Finally, it is embedded in the surface of the material in an intercalation form to achieve the purpose of electron transfer.

[0031] Furthermore, in step S1, the method of uniform dispersion is one or more of the following: aqueous solution dissociation, sand milling and / or ball milling, which achieve ionic dispersion of raw materials in the form of mechanical force or shear force.

[0032] Furthermore, in step S2, the protective atmosphere is nitrogen and / or argon, which is a non-oxygen-containing gas, effectively preventing the oxidation and loss of carbon source and ensuring the reduction of transition metal elements during the sintering process of the material.

[0033] Furthermore, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxalate, sodium formate, sodium acetate, sodium sulfate, sodium chloride, sodium nitrate, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium dodecyl sulfonate, sodium citrate, and / or sodium polyacrylate.

[0034] The metal source M is an Fe source, a Mn source, a V source, and / or a Ti source; the Fe source is one or more of ferric nitrate, ferric sulfate, ferric hydroxide, ferric oxide, ferric oxide, and / or ferric oxide; the Mn source is one or more of manganese oxide, manganese trioxide, manganese tetroxide, manganese hydroxide, manganese acetate, manganese nitrate, and / or manganese sulfate; the V source is one or more of vanadium pentoxide and / or ammonium metavanadate; and the Ti source is one or more of titanium dioxide, titanium sulfate, tetrabutyl titanate, isopropyl titanate, and / or titanium oxysulfate.

[0035] The carbon source is one or more of the following: citric acid, glucose, sucrose, starch, polyethylene glycol, polyacrylic acid, polyvinyl alcohol, graphene, carbon nanotubes and / or carbon black.

[0036] Furthermore, the positive electrode material of the polyanionic sodium-ion battery is sodium iron phosphate, sodium fluorinated iron phosphate, NASICON-type sodium vanadium phosphate, sodium fluorinated vanadium phosphate, sodium vanadium oxyphosphate, sodium fluorinated vanadium oxyphosphate, sodium iron sulfate, sodium fluorinated iron sulfate, sodium manganese titanium phosphate, sodium manganese vanadium phosphate, sodium manganese iron phosphate, sodium pyrophosphate, sodium pyrophosphate, sodium iron phosphate, sodium titanium phosphate, etc., or modified materials of the above materials.

[0037] In this invention, nanoscale metal oxides are used as conductors to modify the interface of polyanionic materials. These oxides have a narrow Fermi bandgap and a low electron transition barrier, resulting in high electron transport capability. Their uniform coating at the material interface can effectively improve the electron transport capability between material particles and the stability of the material interface, thereby reducing the ohmic resistance of the electrode and improving the rate performance and cycle stability of the electrode.

[0038] Application Example 1: Synthesis and Electrochemical Performance of Na4Fe3(PO4)2P2O7 / C / CuO Step S1: Disperse ferric nitrate and sodium dihydrogen phosphate evenly in water at a molar ratio of 3:4 to obtain a precursor solution, wherein the amount of glucose added is 20% of the molar amount of ferric nitrate; Step S2: The above precursor solution is subjected to high-temperature pyrolysis at 400°C to obtain pre-crystalline precursor powder. At this temperature, the iron ions generated by the decomposition of ferric nitrate and sodium dihydrogen phosphate initially complex and crystallize to form pre-crystalline powder with a primary particle size of about 500 nm. In step S3, the nano-sized copper oxide has a particle size of about 10 nm. The difference in particle size allows the nano-sized copper oxide to easily adhere to the surface of the material.

[0039] Step S3: The pre-crystalline precursor powder and nano-sized copper oxide (3wt%) are mixed and coated at 300°C to generate a uniformly coated conductive product. At this temperature, the pre-crystalline powder will not crystallize further, thus ensuring the integrity of its primary particles. The smaller particle size and larger surface energy of the nano-sized copper oxide will embed into the surface of the material at this temperature, which is beneficial to the formation of interfacial chemical bonds and the construction of the interparticle electronic conductive network in step S4.

[0040] Step S4: The conductive product is sintered at 550°C in a nitrogen atmosphere for 10 hours, and then allowed to cool naturally to obtain the Na4Fe3(PO4)2P2O7 / C / CuO material. In this step, the pre-crystalline powder modified with nano-copper oxide further crystallizes and grows into larger single-crystal particles, while covalent bonds are formed at the interface between the two, and a dotted conductive network is formed between the particles.

[0041] Na4Fe3(PO4)2P2O7 / C / CuO, AB, and PVDF were mixed in a mass ratio of 7:2:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 150µm four-sided coating apparatus. The membrane was then dried in a vacuum oven at 100°C for 2 hours. The electrode membrane was punched into a 0.6mm radius disc using a die-casting machine. Using metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator, a CR2016 button cell was assembled in a glove box.

[0042] Figure 1 The image shows the EDS spectrum of the Na4Fe3(PO4)2P2O7 / C / CuO material. The bright gray area represents the Cu signal in the material interface coating layer. The uniform distribution of Cu element signals on the surface indicates that nano-sized copper oxide is uniformly coated on the surface of the material.

[0043] The above-mentioned button cells were subjected to constant current charge-discharge tests with a current density of 0.1C (1C=129mAh / g). Figure 2 The first-cycle charge-discharge curves of the Na4Fe3(PO4)2P2O7 / C / CuO electrode are shown. Within the voltage range of 2.0-4.3V, the reversible specific capacity of the electrode is 110mAh / g, and the average discharge potential is 3.05V, exhibiting a high capacity utilization rate. This is related to the small grain size of the material and the large number of effective sodium insertion / extraction in the structure.

[0044] Application Example 2: Synthesis and Electrochemical Performance of Na3V2(PO4)3 / C / NiO Step S1: Vanadium pentoxide and sodium dihydrogen phosphate are dispersed evenly in water at a molar ratio of 0.5:3.0 to obtain a precursor solution, wherein the amount of glucose added is 15% of the molar amount of ferric nitrate; Step S2: The above precursor solution is subjected to high-temperature pyrolysis at 500°C to obtain pre-crystalline precursor powder. At this temperature, the interface of vanadium pentoxide and sodium dihydrogen phosphate will initially melt and react to generate a pre-crystalline shell-core structure. The particle size of the shell-core structure is about 600 nm, while the particle size of the nano-sized nickel oxide in step S3 is about 15 nm. The large difference in particle size is beneficial to the adsorption and embedding of nano-sized nickel oxide on the shell surface during the subsequent mixing and coating process.

[0045] Step S3: The pre-crystalline precursor powder and nano-sized nickel oxide (2.5 wt%) are mixed and coated at 400°C to generate a uniformly coated conductive product. At this temperature, the core-shell structure of the pre-crystalline powder is still intact, while the nano-sized nickel oxide will be embedded into the surface shell of the material. During the sintering process in step S4, the oxygen atoms in the nickel oxide will form PO chemical bonds with the phosphorus atoms in the phosphate group, and an electronic conductive network will be established between the particles.

[0046] Step S4: The conductive product is sintered at 700°C in a nitrogen atmosphere for 17 hours, and then allowed to cool naturally to obtain the Na3V2(PO4)3 / C / NiO material. In this step, the pre-crystalline powder modified with nano-sized nickel oxide grows epitaxially along the crystal lattice into single-crystal particles with higher crystallinity, and the particles are interconnected by a dotted conductive network formed by nano-sized nickel oxide.

[0047] Na3V2(PO4)3 / C / NiO, AB, and PVDF were mixed in a mass ratio of 7:2:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 150µm four-sided coating apparatus. The membrane was then dried in a vacuum drying oven at 100°C for 2 hours. The electrode membrane was punched into a 0.6mm radius disc using a die-casting machine. Using metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator, a CR2016 button cell was assembled in a glove box.

[0048] The aforementioned coin cell was subjected to constant current charge-discharge testing at a current density of 0.1C (1C = 121 mAh / g). Electrochemical performance tests showed that within a voltage range of 2.0-4.3V, the electrode exhibited a reversible specific capacity of 115 mAh / g and an average discharge potential of 3.4V, demonstrating high capacity utilization. Furthermore, at a 10C rate, the electrode retained 94% of its capacity compared to a 0.1C rate, and after 1000 cycles, the capacity retention reached 98%, demonstrating excellent rate performance and cycle stability. This indicates that the presence of the nano-sized copper oxide coating significantly improved the electronic conductivity between materials, reduced contact resistance, and effectively reduced electrolyte corrosion, thereby enhancing the material's rate performance and cycle stability.

[0049] Application Example 3: Synthesis and Electrochemical Performance of Na3MnTi(PO4)3 / C / ZnO Step S1: Disperse manganese trioxide, titanium dioxide, and sodium dihydrogen phosphate evenly in water at a molar ratio of 0.5:1:3 to obtain a precursor solution, wherein the amount of glucose added is 12% of the molar amount of ferric nitrate; Step S2: The above precursor solution is subjected to high-temperature pyrolysis at 450°C to obtain precrystalline precursor powder. At this temperature, manganese trioxide, dioxide, and sodium dihydrogen phosphate will pyrolyze to generate manganese-based, titanium-based, and manganese-titanium-based precrystalline substances. The particle size distribution of this material is about 500-650 nm, while the nano-sized zinc oxide in step S3 has a particle size of about 12 nm. The smaller zinc oxide particles are easily adsorbed on the surface of the material.

[0050] Step S3: The pre-crystalline precursor powder and nano-sized zinc oxide (2.0 wt%) are mixed and coated at 380°C to generate a uniformly coated conductive product. At this temperature, the pre-crystalline powder will not crystallize further, while the nano-sized zinc oxide will be embedded into the surface of the material at high temperature. During the sintering process in step S4, the zinc oxide forms chemical bonds with the material interface and bonds with each other between particles to achieve rapid electron transport.

[0051] Step S4: The conductive product is sintered at 650°C in a nitrogen atmosphere for 14 hours, followed by natural cooling to obtain the Na3MnTi(PO4)3 / C / ZnO material. In this step, the pre-crystalline powder modified with nano-zinc oxide generates particles with higher crystallinity, and the zinc oxide acts as a bridge for electron transport between particles, improving the electronic conductivity of the material and reducing its internal resistance.

[0052] Na3MnTi(PO4)3 / C / ZnO, AB, and PVDF were mixed in a mass ratio of 7:2:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 150µm four-sided coating apparatus. The membrane was then dried in a vacuum oven at 100°C for 2 hours. The electrode membrane was punched into a 0.6mm radius disc using a die-casting machine. Using metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator, a CR2016 button cell was assembled in a glove box.

[0053] The aforementioned coin cell was subjected to constant current charge-discharge testing at a current density of 0.1C (1C = 165 mAh / g). Electrochemical performance tests showed that within a voltage range of 1.5-4.3V, the electrode exhibited a reversible specific capacity of 155 mAh / g and an average discharge potential of 3.45V, demonstrating high capacity utilization. Furthermore, at a 10C rate, the electrode retained 96% of its capacity compared to a 0.1C rate, and after 1000 cycles, the capacity retention remained as high as 96%, showcasing excellent rate performance and cycle stability. This indicates that the presence of the nano-sized zinc oxide coating contributes to improving the electronic conductivity between material particles, thereby reducing contact resistance. Simultaneously, the presence of the zinc oxide interfacial coating also prevents electrolyte corrosion, further enhancing the material's rate performance and cycle stability.

[0054] Comparative Example 1: Synthesis and Electrochemical Performance of Na4Fe3(PO4)2P2O7 / C Step S1: Disperse ferric nitrate and sodium dihydrogen phosphate evenly in water at a molar ratio of 3:4 to obtain a precursor solution, wherein the amount of glucose added is 20% of the molar amount of ferric nitrate; Step S2: The above precursor solution is subjected to high-temperature pyrolysis at 400°C to obtain pre-crystalline precursor powder; Step S3: The pre-crystallized precursor powder is sintered at 550°C in a nitrogen atmosphere for 10 hours. After natural cooling, the Na4Fe3(PO4)2P2O7 / C material is obtained.

[0055] Na4Fe3(PO4)2P2O7 / C, AB, and PVDF were mixed in a mass ratio of 7:2:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 150µm four-sided coating apparatus. The membrane was then dried in a vacuum drying oven at 100°C for 2 hours. The electrode membrane was punched into a 0.6mm radius disc using a die-cutting machine. Using metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator, a CR2016 button cell was assembled in a glove box.

[0056] The above-mentioned button cells were subjected to constant current charge-discharge tests with a current density of 0.1C (1C=129mAh / g). Figure 2 The first-cycle charge-discharge curve of the Na4Fe3(PO4)2P2O7 / C electrode is shown. Within the voltage range of 2.0-4.3V, the reversible specific capacity of the electrode is 101mAh / g, and the average discharge potential is 3.00V. The capacity utilization rate is lower than that of Example 1. This is related to the fact that during the secondary sintering of the material, it continued to grow without the obstruction of nano-state oxides, resulting in larger grains and a reduction in the effective number of sodium insertions and extractions in the structure.

[0057] Compared to Example 1, the material in Comparative Example 1 at a 10C magnification ( Figure 3 The capacity retention rate at 0.1C was 87%, which is related to the material's low electronic conductivity, indicating that simple carbon coating cannot effectively reduce the interfacial contact resistance, thus weakening the electronic transition capability between materials. Furthermore, this electrode at 1C... Figure 4 After 1000 cycles, the capacity retention rate was only 94%, indicating that the material had some side reactions with the electrolyte during the cycling process, which led to the pulverization and cracking of the material interface, thereby reducing the stability of the material.

[0058] Compared to Comparative Example 1, in Example 1 the material was subjected to a 10C magnification ( Figure 3 The capacity retention rate was 95% at 0.1C. This high capacity retention is related to the material's high electronic conductivity, indicating that the coating of nano-sized copper oxide can effectively reduce the interfacial contact resistance and improve the electronic transition capability between materials. Furthermore, this electrode maintains a capacity retention rate of 95% at 0.1C. Figure 4 After 1000 cycles, the capacity showed almost no decay, indicating that the coating of nano-sized copper oxide effectively reduced the side reactions between the material interface and the electrolyte, and improved the stability of the material.

[0059] Comparative Example 2: Synthesis and Electrochemical Performance of Na3V2(PO4)3 / C Step S1: Vanadium pentoxide and sodium dihydrogen phosphate are dispersed evenly in water at a molar ratio of 0.5:3.0 to obtain a precursor solution, wherein the amount of glucose added is 15% of the molar amount of ferric nitrate; Step S2: The above precursor solution is subjected to high-temperature pyrolysis at 500°C to obtain pre-crystalline precursor powder; Step S3: The pre-crystallized precursor powder is sintered at 700°C in a nitrogen atmosphere for 17 hours. After natural cooling, the Na3V2(PO4)3 / C material is obtained.

[0060] Na3V2(PO4)3 / C, AB, and PVDF were mixed in a mass ratio of 7:2:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 150µm four-sided coating apparatus. The membrane was then dried in a vacuum drying oven at 100°C for 2 hours. The electrode membrane was punched into a 0.6mm radius disc using a die-cutting machine. Using metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1 vol%)+5% FEC as the electrolyte, and a PP / PE / PP three-layer separator, a CR2016 button cell was assembled in a glove box.

[0061] The coin cell was subjected to constant current charge-discharge testing at a current density of 0.1C (1C = 121 mAh / g). Electrochemical performance tests showed that within a voltage range of 2.0-4.3V, the reversible specific capacity of the electrode was 103 mAh / g, and the average discharge potential was 3.35V, indicating a lower capacity utilization rate compared to Example 2. Furthermore, at a 10C rate, the capacity retention was only 81% of that at a 0.1C rate, and after 1000 cycles, the capacity retention was only 82%. Compared to Example 2, its rate performance and cycle stability were not improved, indicating that carbon coating alone cannot effectively improve the electronic conductivity between materials, leading to increased contact resistance and poorer rate performance. Simultaneously, the corrosiveness of the electrolyte reduces the material's structure and cycle stability.

[0062] Comparative Example 3: Synthesis and Electrochemical Performance of Na3MnTi(PO4)3 / C Step S1: Disperse manganese trioxide, titanium dioxide, and sodium dihydrogen phosphate evenly in water at a molar ratio of 0.5:1:3 to obtain a precursor solution, wherein the amount of glucose added is 12% of the molar amount of ferric nitrate; Step S2: The above precursor solution is subjected to high-temperature pyrolysis at 450°C to obtain pre-crystalline precursor powder; Step S3: The pre-crystallized precursor powder is sintered at 650°C in a nitrogen atmosphere for 14 hours. After natural cooling, Na3MnTi(PO4)3 / C material is obtained.

[0063] Na3MnTi(PO4)3 / C, AB, and PVDF were mixed in a mass ratio of 7:2:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 150µm four-sided coating apparatus. The membrane was then dried in a vacuum drying oven at 100°C for 2 hours. The electrode membrane was punched into a 0.6mm radius disc using a die-cutting machine. Using metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator, a CR2016 button cell was assembled in a glove box.

[0064] The aforementioned coin cell was subjected to constant current charge-discharge testing at a current density of 0.1C (1C = 165 mAh / g). Electrochemical performance tests showed that within a voltage range of 1.5-4.3V, the reversible specific capacity of the electrode was 134 mAh / g, with an average discharge potential of 3.40V, indicating low capacity utilization. Furthermore, at a 10C rate, the electrode retained 81% of its capacity compared to a 0.1C rate, and after 1000 cycles, the capacity retention was only 86%. Compared to Application Example 3, this demonstrated poorer rate performance and cycle stability, indicating that the presence of a single carbon coating layer cannot meet the material's electronic conductivity requirements, resulting in higher contact resistance, increased polarization, and decreased electrochemical performance. Simultaneously, electrolyte decomposition at the material interface negatively impacts the material's structure and cycle stability.

[0065] The above embodiments are merely specific examples of the present invention, and their descriptions are quite specific and detailed, but they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these obvious substitutions all fall within the protection scope of the present invention.

Claims

1. A method for preparing a polyanionic sodium-ion battery cathode material with an interface modification layer, characterized in that... Includes the following steps: S1. Preparation of precursor solution: Sodium source, metal M source, anion source and carbon source are dispersed evenly in water according to the stoichiometric ratio in the molecular formula of polyanionic cathode material to obtain precursor solution. S2. Preparation of precrystalline precursor powder: The precursor solution obtained in step S1 is subjected to high-temperature pyrolysis under a protective atmosphere to obtain precrystalline precursor powder. S3. Pre-coating of precursor powder: The pre-crystalline precursor powder obtained in step S2 is mixed with nano-sized conductive metal oxide in a certain proportion and the interface is modified in a high-temperature coating machine to form a uniform pre-coated powder; the high-temperature coating temperature range is 300-500℃, and the nano-sized conductive metal oxide is one or more of ruthenium dioxide, tin dioxide, indium tin oxide, indium oxide, nickel oxide, iron oxide, silver oxide, zinc oxide, and copper oxide; S4. High-temperature sintering preparation: The pre-coated powder obtained in step S3 is sintered at high temperature in a protective atmosphere to obtain a polyanion sodium-ion battery cathode material with an interface modification layer. The positive electrode material of the polyanionic sodium-ion battery is sodium iron phosphate, sodium fluorinated iron phosphate, NASICON-type sodium vanadium phosphate, sodium fluorinated vanadium phosphate, sodium vanadium oxyphosphate, sodium fluorinated vanadium oxyphosphate, sodium iron sulfate, sodium fluorinated iron sulfate, sodium manganese titanium phosphate, sodium manganese vanadium phosphate, sodium manganese iron phosphate, sodium pyrophosphate, sodium pyrophosphate, and sodium titanium phosphate.

2. The method for preparing the polyanionic sodium-ion battery cathode material with an interface modification layer according to claim 1, characterized in that: In step S2, the high-temperature pyrolysis temperature range is 200-500℃.

3. The method for preparing the polyanionic sodium-ion battery cathode material with an interface modification layer according to claim 1, characterized in that: In step S3, the nano-state metal conductive oxide accounts for 0.1-10% of the weight of the pre-crystalline precursor powder.

4. The method for preparing the polyanionic sodium-ion battery cathode material with an interface modification layer according to claim 1, characterized in that: In step S4, the high-temperature sintering temperature range is 500-750℃, and the sintering time is 1-20h.

5. The method for preparing the polyanionic sodium-ion battery cathode material with an interface modification layer according to claim 1, characterized in that: In step S1, the method of uniform dispersion is sand milling and / or ball milling.

6. The method for preparing the polyanionic sodium-ion battery cathode material with an interface modification layer according to claim 1, characterized in that: In step S2, the protective atmosphere is nitrogen and / or argon.

7. The method for preparing the polyanionic sodium-ion battery cathode material with an interface modification layer according to claim 1, characterized in that: The sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxalate, sodium formate, sodium acetate, sodium sulfate, sodium chloride, sodium nitrate, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium dodecyl sulfonate, sodium citrate and / or sodium polyacrylate. The metal source M is an Fe source, a Mn source, a V source, and / or a Ti source; the Fe source is one or more of ferric nitrate, ferric sulfate, ferric hydroxide, ferric oxide, ferric oxide, and / or ferric oxide; the Mn source is one or more of manganese oxide, manganese trioxide, manganese tetroxide, manganese hydroxide, manganese acetate, manganese nitrate, and / or manganese sulfate; the V source is one or more of vanadium pentoxide and / or ammonium metavanadate; the Ti source is one or more of titanium dioxide, titanium sulfate, tetrabutyl titanate, isopropyl titanate, and / or titanium oxysulfate. The carbon source is one or more of citric acid, glucose, sucrose, starch, polyethylene glycol, polyacrylic acid, polyvinyl alcohol, graphene, carbon nanotubes and / or carbon black.

Citation Information

Patent Citations

  • Metal-based sodium phosphate salt as sodium ion battery positive electrode material and preparation method thereof

    CN116154151A

  • Carbon-sulfur coated polyanionic sodium ion battery positive electrode material and preparation method thereof

    CN116207267A